Special Issue: Viral Infections in Companion Animals - Margaret J. Hosie; Regina Hofmann-Lehmann (Viruses, 2022)
Companion animals, such as cats, dogs, horses and exotic species, play an important role in society; more than 600 million cats and 900 million dogs live closely with humans worldwide [...]